ABOUT DIFFERENCE OF SOLUTION SINGULAR DISTURBED AND UNDISTURBED BOUNDARY PROBLEMS - Imangaliyev, Y.I. (Recent Contributions to Physics, 2018)
In work obtained the asymptotical convergence of solution singular disturbed integral boundary problem for linear integral differential equation of type Fredholm to solution undisturbed integral boundary problem.